OPTIMIZATION OFT ANDEM SOLAR CELL FOR HYDROGEN PRODUCTION - BASHIRI, ROBABEH (2016)
Solar hydrogen production through water photosplitting by photoelectrochemical (PEC) cell is one of the most desirable, cost-effective and environmentally friendly processes but still sutl'ering from a low efficiency. To improve its efficiency, a tandem solar cell was made up by connecting a dye solar cell (DSC) with the modified PEC cell in a series. Tandem solar cell was fabricated through a simple and cheap process, working with solar energy and water, which are both abundant and renewable. A series of monometallic (Cu and Ni) and bimetallic (Cu-Ni) doped TiOz as novel photocatalysts were synthesized using sol-gel hydrothermal method. The physicochemical properties of the calcined photocatalysts were investigated by different analytical techniques whilst their photoelectrochemical behavior were analyzed using electrochemical impedance spectroscopy. photocurrent density, photoconversion efficiency and Matt-Schottky analysis.